2013
DOI: 10.1007/s12664-013-0365-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Manning, Rome I, II, and III, and Asian diagnostic criteria: Report of the Multicentric Indian Irritable Bowel Syndrome (MIIBS) study

Abstract: By Manning's and the Asian criteria, a diagnosis of IBS was made frequently among Indian patients with chronic functional lower GI symptoms with no alarm features; the Rome II criteria gave the lowest yield. By the stool frequency criteria, a majority of patients had unclassified pattern, unlike by the stool form and patients' perception of their symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…As the identification and classification of FGIDs are dependent entirely on the ability of patients to describe and of the clinicians and investigators to interpret symptoms, we wonder if these criteria would do well in diagnostic allocation, sub-typing and treatment assignment uniformly throughout the world. 4 In epidemiologic, pathophysiologic and therapeutic studies of FGIDs, the Rome Criteria have been applied almost universally. Epidemiological studies from Asia suggest that the prevalence and spectrum of FGIDs may differ in Asia compared to the West.…”
Section: Introductionmentioning
confidence: 99%
“…As the identification and classification of FGIDs are dependent entirely on the ability of patients to describe and of the clinicians and investigators to interpret symptoms, we wonder if these criteria would do well in diagnostic allocation, sub-typing and treatment assignment uniformly throughout the world. 4 In epidemiologic, pathophysiologic and therapeutic studies of FGIDs, the Rome Criteria have been applied almost universally. Epidemiological studies from Asia suggest that the prevalence and spectrum of FGIDs may differ in Asia compared to the West.…”
Section: Introductionmentioning
confidence: 99%
“…; in a recent multi-center study from India, improvement in sub-typing IBS using this approach has been reported 30 ; in this study, applying stool types 3 (as hard stool) and 5 (as soft stool) as abnormal stool forms actually allowed more patients to be sub-typed. 30 Another reason for poor acceptance of the Rome criteria in clinical practice, particularly in Asia, has been the need for maintaining a bowel diary indicating Bristol stool forms for 2 weeks before IBS could be sub-typed.…”
mentioning
confidence: 80%
“…30,31 For example, in 2 Indian studies, as high as 26/191 (13.6%) and 134/190 (70%) patients with IBS could not be sub-typed by the Rome III criteria. 30 This might be related to difference in stool frequency, form and gut transit time in the West as compared to Asia. According to the Rome criteria, only Bristol type 1 and 2 stools are considered to denote constipation.…”
Section: Limitations Of Rome IV Criteria For Irritable Bowel Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Since FGIDs are diagnosed by symptoms-based criteria, 1,12 and symptoms are influenced by psychosocial and socio-cultural factors, [8][9][10][11] there has been concern whether the Rome III questionnaire in its original form would be similarly applicable for uniform diagnosis, sub-typing, and treatment allocation for FGIDs throughout the world. 11,13 To overcome some of the above-mentioned limitations, the Enhanced Asian Rome III questionnaire (EAR3Q) 14 has been developed by the Asian experts by consensus, which is a culturally adapted version of the Rome III diagnostic questionnaire (R3DQ). 15 Bengali is one of the most spoken languages and is ranked seventh in the world.…”
Section: Introductionmentioning
confidence: 99%